Navigating Patient Comfort: Gendered Perspectives on Medical Student Involvement in Healthcare Interactions in Peshawar, Pakistan : Gendered Perspectives on Medical Student Involvement - Zahir, Salman; Khan, Khansa; Jahan, Sarwat; Mazhar, Somia; Hussain, Sulaiman; Khan, Zee Shan; Ahmad Khan, Zahoor; Bangash, Ismail (Pakistan Journal of Health Sciences, 2023)
Patient interactions are fundamental to medical education, influencing the training of medical students and shaping their clinical understanding. Objective: To probe patient perspectives on the presence of medical students during consultations, clinical examinations and surgical procedures, with a focus on identifying gender-based differences in preferences and comfort levels. Methodology: This cross-sectional study was conducted in tertiary care hospitals in Peshawar involving 500 patients from Northwest General Hospital and Research Center and Northwest Teaching Hospital, data collected through a self-structured questionnaire revealed distinct gender disparities. Results: Male participants generally exhibited higher approval and comfort levels with medical student involvement, particularly during consultations, examinations, and surgery. Variations were evident in preferences related to medical history taking, comfort during physical examinations, and willingness to permit students in the operating room. Patients underscored the importance of recognizing gender preferences in medical student interactions. Conclusions: This study emphasized the significance of tailoring medical education practices to address gender-specific variations, ensuring a patient-centered approach and fostering positive healthcare experiences for all.